2017
DOI: 10.1371/journal.pone.0173565
|View full text |Cite
|
Sign up to set email alerts
|

A KCNC3 mutation causes a neurodevelopmental, non-progressive SCA13 subtype associated with dominant negative effects and aberrant EGFR trafficking

Abstract: The autosomal dominant spinocerebellar ataxias (SCAs) are a diverse group of neurological disorders anchored by the phenotypes of motor incoordination and cerebellar atrophy. Disease heterogeneity is appreciated through varying comorbidities: dysarthria, dysphagia, oculomotor and/or retinal abnormalities, motor neuron pathology, epilepsy, cognitive impairment, autonomic dysfunction, and psychiatric manifestations. Our study focuses on SCA13, which is caused by several allelic variants in the voltage-gated pota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 67 publications
1
25
0
Order By: Relevance
“…CDCP1 Pten -/-MEFs also stained negative for SA-β-gal and exhibited increased cell proliferation with an elongated phenotype when compared with Pten -/-MEFs (Supplemental Figure 6A). a tumor-like phenotype (35,36). We found that overexpression of CDCP1-WT, but not CDCP1-delta, promoted extra macrochaetae formation.…”
Section: Crpc and Metastatic Prostate Tumors Exhibit Elevated Expressmentioning
confidence: 69%
See 1 more Smart Citation
“…CDCP1 Pten -/-MEFs also stained negative for SA-β-gal and exhibited increased cell proliferation with an elongated phenotype when compared with Pten -/-MEFs (Supplemental Figure 6A). a tumor-like phenotype (35,36). We found that overexpression of CDCP1-WT, but not CDCP1-delta, promoted extra macrochaetae formation.…”
Section: Crpc and Metastatic Prostate Tumors Exhibit Elevated Expressmentioning
confidence: 69%
“…The frequency of tumors displaying a low level of Table 1. CDCP1-positive samples in BPH, RPE, CRPC, and metastatic PCa in human prostate cancers BPH RPE CRPC Metastasis Total 45 382 102 35 CDCP1-positive 4 65 45 18 For TMA1, n = 564. form of CDCP1 (CDCP1-delta) lacking Src-phosphorylation sites (35,36) in Drosophila melanogaster. The Drosophila larval imaginal discs are a monolayer epithelium that is considered morphologically comparable to mammalian epithelia and therefore constitutes an ideal system in which to model cancer progression in vivo (37).…”
Section: Crpc and Metastatic Prostate Tumors Exhibit Elevated Expressmentioning
confidence: 99%
“…Indeed, incorporation of KCNC3 R420H into the channel reduced the excitability of fast-spiking motoneurons and impaired startle reflex in zebrafish (Issa et al, 2011). The design of our PC-specific vector will allow the investigation of the cell biological mechanisms underlying the cytotoxicity of this mutant allele, including the change of electrophysiological properties (Issa et al, 2011) as well as an impaired intracellular trafficking as has been recently suggested (Gallego-Iradi et al, 2014;Khare et al, 2017). A slight drawback of zebrafish cerebellar disease modeling though may arise from only a few differences in cerebellar cytoarchitecture compared with mammals.…”
Section: Cross-species Cpce Activity In Pcsmentioning
confidence: 86%
“…Other familial potassium channelopathies associated with cerebellar dysfunction include spinocerebellar ataxia type 13 (SCA13), episodic ataxia type 1 (EA1), and sensorineural deafness, ataxia, mental retardation, and electrolyte imbalance (SESAME syndrome) which are caused by mutations in the KCNC3 , KCNA1 , and KCNJ10 genes, respectively [ 25 27 ]. Different to SCA13 in which some patients have a non-progressive course [ 28 ], SCA19/22 is clearly progressive [ 6 , 7 ]. Interestingly, an association between epilepsy and long QT syndrome (LQTS) has been proposed for mutations in KCNQ1 ; however, ataxia is, to the best of our knowledge, not part of the disease spectrum associated with KCNQ1 mutations [ 29 ].…”
Section: Discussionmentioning
confidence: 99%